Optimization Process of Compound Probiotic Fermented Feed and Feeding Effect on Shrimp - Guotao ZHANG; Xin YU; Luqing PAN (Progress in Fishery Sciences)
In this study, three efficient probiotic strains, Bacillus subtilis, Enterococcus faecium, and Saccharomyces cerevisiae, isolated from the intestine of Penaeus vannamei, were selected as fermentation strains. This study focused on optimizing the process conditions of compound probiotic fermented feed by orthogonal experiments and investigating the effects on growth performance, digestion, and immunity function of P. vannamei fed with fermented feeds, with the aim of improving the nutritional performance of the compound feed and establishing a fermentation technology for shrimp feed. The results showed that with an inoculation ratio of the three strains of 1%: 1%: 1%, the process conditions of three efficient fermented feeds (the lowest pH group, the highest acid-soluble protein group, and the highest acid polysaccharide group) were obtained by optimizing the fermentation temperature, water ratio, and fermentation time through orthogonal experiments. During the 28-day feeding experiment, shrimp fed the three fermented feed groups exhibited an increase in survival rate, weight gain rate, and specific growth rate. The lowest pH and highest acid-soluble protein groups had significantly lower feed conversion rates (P < 0.05). The hepatopancreatic index of shrimp in the lowest pH group and the highest acid-soluble protein group increased significantly, whereas there was no significant difference in the crude lipid content among the three fermented feed groups. In addition, the protease and amylase activities of the hepatopancreas and intestine in the highest acidic polysaccharide group increased significantly (P < 0.05). Compared with the control group, the total hemocyte count and phagocytosis rate were the highest in the highest acidic polysaccharide group, followed by the lowest pH and highest acid-soluble protein groups. The gene expression of Pen3 and Crustin in hemocytes increased significantly, whereas the expression of Pen3, Crustin, and ALF increased significantly in the intestine (P < 0.05). However, the expression levels of inflammatory factors did not differ significantly among the three fermented feed groups. In conclusion, the three fermented feed groups, obtained by optimizing the fermentation process of the three probiotic strains, significantly improved the growth performance and immune defense level of P. vannamei. After comprehensive evaluation, the acidic polysaccharide group was found to be the most efficient fermentation feed for P. vannamei.